2000
DOI: 10.1212/wnl.55.4.593
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at codon 129 of the prion protein gene is not associated with sporadic AD

Abstract: An association between cognitive performance in elderly people and variability in the codon 129 of the prion protein gene (PRNP) has been recently described. The authors analyzed this polymorphism in 278 sporadic AD patients and 268 cognitively normal control subjects. Analyses stratifying by APOE genotype, age, and gender failed to reveal any association between homozygosity for the 129 PRNP methionine or valine alleles and AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
3
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 8 publications
3
34
3
4
Order By: Relevance
“…In opposition to some studies, which showed interaction between ApoE and PRNP, our data did not reveal differences in codon 129 genotypes according to the ApoE status [13][14][15][16][17][18][19][20][21] . This study of PRNP in patients with AD in the Brazilian population has, as its main limitation, the small sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In opposition to some studies, which showed interaction between ApoE and PRNP, our data did not reveal differences in codon 129 genotypes according to the ApoE status [13][14][15][16][17][18][19][20][21] . This study of PRNP in patients with AD in the Brazilian population has, as its main limitation, the small sample.…”
Section: Discussioncontrasting
confidence: 99%
“…A few studies have shown that this polymorphism may be a risk factor for AD [12][13][14] . Others, however, failed to confirm such association 5,8,[15][16][17][18][19][20][21] . A meta-analysis concluded that codon 129 homozygosity of PRNP is a risk factor for AD in a Caucasian population 19 .…”
mentioning
confidence: 99%
“…Similarly, findings on the influence of PRNP*129Val in the risk of AD, another neurodegenerative disorder, have been well defined despite ethnic background discrepancies. Previous studies have reported that this variant is significantly associated with AD in Dutch [13], German [14], and Polish populations [15], in contrast to the findings from studies involving Korean [16], Spanish [17], and Italian [18] populations. Furthermore, it has been known that homozygosity for codon 129 (M or V allele) is connected with early-onset AD [13,17].…”
Section: Introductioncontrasting
confidence: 64%
“…Thus, our study contrasted with the results obtained from the German and Polish populations but is consistent with that obtained from Japanese that showed no association of the M129V polymorphism with AD regardless of the age at onset or ApoE-4 genotypes. Also, no significant difference was observed in Spanish population and in Italian population (Combarros et al, 2000;Del Bo et al, 2005). With regard to such discrepancy among ethnic groups, meta-analysis of six published reports showed that Caucasian subjects homozygous at codon 129 had a moderate but significant risk [OR = 1.3, 95%, CI: 1.0-1.6, P = 0.05] of developing AD compared to heterozygous individuals (Del Bo et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Also, in Polish population, the MM and VV genotypes were higher in AD patients (Golanska et al, 2004). On the other hand, a study with Spanish sporadic AD patients showed no association between the homozygosity and AD even after stratifying by ApoE genotype, age at onset, and gender (Combarros et al, 2000). The two polymorphisms, M129V and E219K, were not associated with AD (Ohkubo et al, 2003) in Japanese population.…”
Section: Introductionmentioning
confidence: 88%